2016
DOI: 10.1017/erm.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Protein pathways working in human follicular fluid: the future for tailored IVF?

Abstract: The human follicular fluid (HFF) contains molecules and proteins that may affect follicle growth, oocyte maturation and competence acquiring. Despite the numerous studies, an integrated broad overview on biomolecular and patho/ physiological processes that are proved or supposed to take place in HFF during folliculogenesis and oocyte development is still missing. In this review we report, for the first time, all the proteins unambiguously detected in HFF and, applying DAVID (Database for Annotation, Visualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 118 publications
(144 reference statements)
0
43
0
Order By: Relevance
“…In addition , we found that the OS markers in FF and serum concurred. FF originates from blood diffusion and from secretion from GCs and oocytes; thus, OS markers in FF reflect the systemic OS status and that of the ovaries 32 . Through correlation analysis, we found that the basal serum TOS and OSI were both positively correlated with HOMA-IR, FINS and TT levels and negatively correlated with SHBG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition , we found that the OS markers in FF and serum concurred. FF originates from blood diffusion and from secretion from GCs and oocytes; thus, OS markers in FF reflect the systemic OS status and that of the ovaries 32 . Through correlation analysis, we found that the basal serum TOS and OSI were both positively correlated with HOMA-IR, FINS and TT levels and negatively correlated with SHBG.…”
Section: Discussionmentioning
confidence: 99%
“…PMC can only be achieved by blocking the inevitably spontaneous nuclear maturation that starts immediately after the oocyte that has been disconnected from the somatic compartment of the follicle, and extending the period of GV-stage arrest in PMC might alleviate this asynchrony by allowing time for completion of cytoplasmic maturity [4, 6, 42, 43]. As reported, the path to cytoplasmic competence included the buildup and storage of transcripts [4446], synthesis and accumulation of proteins, posttranslational modifications, and ultrastructural changes. The meiotic arrest can be induced pharmacologically by manipulating the intraoocyte cAMP levels [4, 6].…”
Section: Discussionmentioning
confidence: 99%
“…During hyper-ovarian stimulation, ROS accumulates with accelerated metabolic rates for more energy and nutrients [26]. Ovarian antioxidants are numerous, and OS occurs when the natural antioxidant system cannot balance excessive ROS.…”
Section: Discussionmentioning
confidence: 99%